Analysis of the Transformation of Islamic Family Law in the Arab Republic of Egypt - Damsir, Fajrul Islami; Akbarizan (MUI Kota Pekanbaru, 2024)
Among the Muslim countries that codified Islamic family law in the early phases was Egypt. Egypt is the third Muslim country after Turkey and Lebanon to codify Islamic family law. As a country that was once colonized by Europeans and a country that has a beacon of Islamic scholarship called Al-Azhar, studying the reform of Islamic family law in Egypt is an interesting matter. This research is a literature study, and uses a descriptive-analytic approach that originates from books on Islamic family law reform in Muslim countries and Egyptian family law laws related to marriage and inheritance. From the above study, at least several conclusions can be drawn: first, the renewal of Egyptian family law began with the issuance of two Egyptian family laws, namely Law no. 25 of 1920 and Law no. 20 of 1929. The law was then updated in 1979, and updated again in the form of Civil Law no. 100 of 1985. Second, among the reforms in Egyptian family law are reforms in the age limit for marriage, registration of marriages, divorce before the court, polygamy, and obligatory wills. Third, the renewal models used are takhayyur, siyasah syar'iyyah, and text reinterpretation.